2017
DOI: 10.21595/jve.2017.17862
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive interval type-2 fuzzy logic systems for vehicle handling enhancement by new nonlinear model of variable geometry suspension system

Abstract: This research examines the emerging role of adaptive interval type-2 fuzzy logic systems (AIT2FLS) versus adaptive type-1 fuzzy logic system (AT1FLS) in vehicle handling by a new nonlinear model of the variable geometry suspension system (VGS) as a vehicle active suspension system. A proper controller is needed in order to have soft response and robustness against challenging vehicle maneuvers. Two controllers, including AT1FLS and AIT2FLS have been used in the paper. The proposed AIT2FLS can efficiently handl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Subha Celin and Rajeswari [10] have explain the vehicle active suspension system (VASS), T2FLC and GA-T2FLC algorithms are performed, with the T2FLC gains being tuned by an actual encoded genetic algorithm, thus T1FLC is performed (they used same bases of rules previously proposed by Rajeswari [11] but with Gaussian inference functions), the results of his different strategies are compared to the passive system, the study showed the effectiveness of GA-T2FLC. In 2017, [12] examines the emerging role of Adaptive Interval Fuzzy Logic Type-2 (AIT2FLS) versus Adaptive Fuzzy Logic Type-1 ISSN: 0010-8189 © CONVERTER 2020 www.converter-magazine.info 743 (AT1FLS) in vehicle driving by a new nonlinear model of the Variable Geometry Active Suspension System (VGS) as a complete vehicle. Do Xuan Phua and Van Mien [13] have clarify a quarter of a vehicle a new adaptive controller, it has been proposed based on a type-2 fuzzy model integrated into a neural network to solve the dead-band and delay problems of the actuators.…”
Section: Introductionmentioning
confidence: 99%
“…Subha Celin and Rajeswari [10] have explain the vehicle active suspension system (VASS), T2FLC and GA-T2FLC algorithms are performed, with the T2FLC gains being tuned by an actual encoded genetic algorithm, thus T1FLC is performed (they used same bases of rules previously proposed by Rajeswari [11] but with Gaussian inference functions), the results of his different strategies are compared to the passive system, the study showed the effectiveness of GA-T2FLC. In 2017, [12] examines the emerging role of Adaptive Interval Fuzzy Logic Type-2 (AIT2FLS) versus Adaptive Fuzzy Logic Type-1 ISSN: 0010-8189 © CONVERTER 2020 www.converter-magazine.info 743 (AT1FLS) in vehicle driving by a new nonlinear model of the Variable Geometry Active Suspension System (VGS) as a complete vehicle. Do Xuan Phua and Van Mien [13] have clarify a quarter of a vehicle a new adaptive controller, it has been proposed based on a type-2 fuzzy model integrated into a neural network to solve the dead-band and delay problems of the actuators.…”
Section: Introductionmentioning
confidence: 99%